2022
DOI: 10.1101/2022.09.15.508006
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Circadian rhythms in the gut microbiota shape sex differences in host gene expression and metabolism

Abstract: Circadian rhythms in microbial communities regulate a variety of essential homeostatic functions in the intestinal tract and distal tissues. Circadian disruption is often associated with sex-specific disease risk, but studies on circadian rhythms, the microbiome, and health outcomes primarily use male mice or collapse both sexes into one experimental condition. Here, we identify sex differences in diurnal rhythms in the intestinal microbiota, the metabolites they produce, and the expression of host genes, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 132 publications
(142 reference statements)
1
0
0
Order By: Relevance
“…These differences may be explained by underlying sex differences in circadian rhythm biology or the effects of circadian rhythm disruption. Indeed, there are numerous sex differences in circadian rhythms, including the function of the immune, metabolic, and endocrine systems (Munyoki et al, 2022;Walton et al, 2022). Moreover, there are sex differences in the metabolic consequences of circadian rhythm disruption, including the effects of ALAN (Masís-Vargas et al, 2019;Rumanova et al, 2020), simulated shift work (Qian et al, 2019), and jet lag (Feliciano et al, 2019), demonstrating precedence for the observed sex differences in this study.…”
Section: Discussionsupporting
confidence: 61%
“…These differences may be explained by underlying sex differences in circadian rhythm biology or the effects of circadian rhythm disruption. Indeed, there are numerous sex differences in circadian rhythms, including the function of the immune, metabolic, and endocrine systems (Munyoki et al, 2022;Walton et al, 2022). Moreover, there are sex differences in the metabolic consequences of circadian rhythm disruption, including the effects of ALAN (Masís-Vargas et al, 2019;Rumanova et al, 2020), simulated shift work (Qian et al, 2019), and jet lag (Feliciano et al, 2019), demonstrating precedence for the observed sex differences in this study.…”
Section: Discussionsupporting
confidence: 61%